2021
DOI: 10.1111/1365-2664.14023
|View full text |Cite
|
Sign up to set email alerts
|

Inference of local invasion pathways in two invasive crayfish species displaying contrasting genetic patterns

Abstract: The efficient management of invasive alien species (IAS) requires the identification of their introduction pathways. Genetic assessments have proven useful to inform invasion pathways at large (national to worldwide) scales, but studies at local scales are still rare, despite their importance for guiding management. In this study, genetic analyses were used to identify local invasion pathways of two invasive crayfish species (the spiny‐cheek crayfish Faxonius limosus and the red swamp crayfish Procambarus clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Knowledge of the composition of fish communities at the start of our study was limited, with no information about management history. Fish could have been introduced legally, illegally, or as stowaways during fish releases (Paz-Vinas et al, 2021), before our study, so we focused on recent stocking practices and their effects on current communities. Our results are consistent with a predictable shift in community composition previously observed in gravel pit lakes (Zhao et al, 2016) and confirm the influence of fishery management and stocking on the trajectory of community assembly in these ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge of the composition of fish communities at the start of our study was limited, with no information about management history. Fish could have been introduced legally, illegally, or as stowaways during fish releases (Paz-Vinas et al, 2021), before our study, so we focused on recent stocking practices and their effects on current communities. Our results are consistent with a predictable shift in community composition previously observed in gravel pit lakes (Zhao et al, 2016) and confirm the influence of fishery management and stocking on the trajectory of community assembly in these ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…The study area included 34 gravel pit lakes located in the central part of the Garonne floodplain, Haute‐Garonne, France (Figure 1). These gravel pit lakes were located within a 55‐km radius and disconnected from the hydrographical network and other gravel pit lakes (Alp et al, 2016; Paz‐Vinas et al, 2021; Zhao et al, 2016) (Figure 1 and Table S1). Study lakes were distributed along a gradient of maturity (from 17 to 56 years following excavation), maximum depth (ranging from 1.7 to 22.4 m), and surface area (ranging from 0.73 to 47.43 ha; Colas et al, 2021; Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The considerable levels of genetic diversity and the high effective meta-population sizes observed in S. glanis populations at the hydrographical basin scale could be the result of multiple introduction events involving individuals from different genetic sources, as is the case for other aquatic invasive species inhabiting the study area (e.g. the spiny-cheek crayfish Procambarus clarkii; Paz-Vinas et al, 2021). This was also (i) suggested by a previous study having conducted a broader genetic survey at the European scale (Castagné et al, 2023), (ii) evidenced by our genetic clustering analyses, which revealed the presence of four genetically distinct groups of individuals (clusters), and (iii) confirmed by the ABC-RF model-choice procedure we conducted, which provided higher support for demo-evolutionary models involving four genetically-distinct sources of individuals instead of one single source.…”
Section: Genetic Variation Of Silurus Glanis Across the Garonne-dordo...mentioning
confidence: 99%
“…Although being generally conducted from a conservation standpoint (e.g. to identify at-risk populations), joint Ne and Nc assessments may also have an important practical value in the context of biological invasions monitoring and management, as they may help identify, monitor and prioritize invasive populations requiring active population control actions at local scales (Blanchet, 2012;Paz-Vinas et al, 2021). For instance, introduced populations with Ne<50 can be expected to be less likely to establish, be maintained and become invasive compared to introduced populations with Ne>500, due to the expected pervasive genetic effects associated with low effective population sizes and genetic diversities (e.g.…”
Section: Introductionmentioning
confidence: 99%